Electroacupuncture Improves Gastric Emptying in Critically Ill Neurosurgical Patients: A Pilot Study. (20th September 2017) - Kao, Man-Ling; Chen, Yao-Li; Lee, Shu-Ching; Huang, Sung-Yen; Lin, Ping-Yi
Abstract : Objective . To compare the efficacy of combined electroacupuncture and metoclopramide treatment with that of metoclopramide only in improving gastric emptying in critically ill neurosurgical patients. Methods . In this prospective case-control pilot study, a total of 16 adult critically ill mechanically ventilated patients who were treated in the surgical intensive care unit were enrolled. Electrical stimulation was applied to 4 pairs of points (maximum intensity < 9.8 mA at 2 Hz). Patients in the control group received standard treatment with intravenous metoclopramide only. Patients in the experimental group received intravenous metoclopramide plus electroacupuncture treatment once daily for 6 consecutive days. Results . Gastric residual volume in the experimental group (n = 7 ) reduced gradually until the fourth day after treatment with electroacupuncture combined with routine metoclopramide administration. Beginning on the fourth day, residual volume was maintained at less than 200 ml per day for the following two days. In the control group (n = 9 ), there was a gradual reduction in residual volume during the first four days followed by a rebounding increase over the next two days. Conclusions . Electroacupuncture combined with intravenous metoclopramide is a more effective treatment for gastric emptying than metoclopramide alone in adult critically ill patients with impaired brain function.